Lowered cutoff of lymph node fine-needle aspiration thyroglobulin in thyroid cancer patients with serum anti-thyroglobulin antibody - Jo, Kwanhoon; Kim, Min-Hee; Lim, Yejee; Jung, So-Lyung; Bae, Ja-Seong; Jung, Chan-Kwon; Kang, Moo-Il; Cha, Bong-Yun; Lim, Dong-Jun (European journal of endocrinology, 2015)
ObjectiveFine needle aspiration cytology (FNAC) and measurement of thyroglobulin (Tg) in needle washout (FNA-Tg) are recommended for the diagnosis of metastatic or recurrent lymph nodes (LNs) in differentiated thyroid cancer (DTC). However, the effect of serum Tg antibody (TgAb) on FNA-Tg levels still remains unclear in the preoperative setting. We analyze the interference of serum TgAb on FNA-Tg levels as proof of concept in the diagnostic advantage of serum TgAb combined with FNA-Tg.Subjects and methodsA total of 370 suspicious cervical LNs from 273 patients with DTC were included. The primary tumor was confirmed as DTC on preoperative pathology in all patients. We performed FNA-Tg measurement and FNAC on suspicious LNs and evaluated the diagnostic performance of FNAC and FNA-Tg according to TgAb status. Final diagnoses were confirmed by histological examination of excised specimens or by follow-up ultrasonography for at least 6 months.ResultsData from 273 subjects with suspicious 370 LNs were evaluated. Fifty-five LNs (14.9%) were from TgAb+ positive serum TgAb (TgAb+) patients. Serum Tg and FNA-Tg levels were significantly lower in patients with TgAb+ than in those with TgAb-negative (TgAb−). Final pathology confirmed 109 LNs (29.5%) asmalignant. Diagnostic performance of FNA-Tg at the same cutoff level was lower in the TgAb+ than TgAb− group. FNA-Tg cutoff levels determined by ROC curve were lower in the TgAb+ group.ConclusionThe results suggested that the cutoff value of FNA-Tg should be lowered in suspicious LN before thyroidectomy in thyroid cancer patients with TgAb.